2017
DOI: 10.14430/arctic4648
|View full text |Cite
|
Sign up to set email alerts
|

Movements and Inferred Foraging by Bowhead Whales in the Canadian Beaufort Sea during August and September, 2006–12

Abstract: Each spring, most bowhead whales of the Bering-Chukchi-Beaufort (BCB) population migrate to the southeast Beaufort Sea and summer in Canadian waters. In August and September, they form aggregations, which are known to occur mainly in the shallow, shelf waters when oceanographic conditions promote concentration of their zooplankton prey. The movements of individual bowheads while they occupy these late summer habitats are less well known; our knowledge is based on photographic evidence and limited tagging studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…This trend of arriving in the Canadian Beaufort Sea in late April and departing in October is consistent with telemetry studies of this population (Mate et al 2000;Citta et al 2015;Harwood et al 2017) and long-term monitoring in Alaska (Braham et al 1980). Citta et al (2015) specifically demonstrated that bowhead whales use the polynya at Cape Bathurst early in the season, which stretches from the Tuktoyaktuk Peninsula to Cape Bathurst and north towards Banks Island, and later in the season, bowhead whales mostly use the shallow shelf adjacent to the Tuktoyaktuk Peninsula.…”
Section: Bowhead Whalessupporting
confidence: 86%
See 3 more Smart Citations
“…This trend of arriving in the Canadian Beaufort Sea in late April and departing in October is consistent with telemetry studies of this population (Mate et al 2000;Citta et al 2015;Harwood et al 2017) and long-term monitoring in Alaska (Braham et al 1980). Citta et al (2015) specifically demonstrated that bowhead whales use the polynya at Cape Bathurst early in the season, which stretches from the Tuktoyaktuk Peninsula to Cape Bathurst and north towards Banks Island, and later in the season, bowhead whales mostly use the shallow shelf adjacent to the Tuktoyaktuk Peninsula.…”
Section: Bowhead Whalessupporting
confidence: 86%
“…These authors still identified the area around Sachs Harbour as a 95% core use area, but it was not as well used as the Cape Bathurst polynya or the Tuktoyaktuk Peninsula. Harwood et al (2017) found similar core use areas for juvenile bowhead whales, but also found that juvenile bowhead whales spent quite a bit of time moving around Banks Island and identified a few core use areas farther north. One acoustic study (Clark et al 2015) recorded in August and September 2009 and 2010 near Tuktoyaktuk found the presence of bowhead whale calls nearly every day, which confirms that bowhead whales stay in the Canadian Beaufort Sea into September.…”
Section: Bowhead Whalesmentioning
confidence: 62%
See 2 more Smart Citations
“…The BCB population overwinters in the Chukchi and the northern Bering Seas and spends the summer in the Alaskan and Canadian Beaufort Sea (Moore and Reeves 1993;Schell and Saupe 1993;Moore et al 2010;Harwood et al 2017). The EC-WG population overwinters in Hudson Strait, northern Hudson Bay, east of Baffin Island, and near the ice edge along West Greenland (Koski et al 2006;HeideJørgensen et al 2007;Ferguson et al 2010).…”
Section: Introductionmentioning
confidence: 99%